The Urban Forests Affecting the Environmental Parameters in Makassar City, Indonesia - Mukrimin; Hasanuddin, Hasanuddin; Sultan, Sultan; Pratiwi, Asti; Hartati, Wahjuni (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
The urban forests in every city are very important to creating comfortable urban conditions for the community. The existence of urban forests, such as city parks, urban forests, and fields, can provide a sense of comfort to the community both thermally and visually. In addition, urban forests also act as microclimate ameliorators and noise reducers. The importance of this research is that it is expected to provide additional information and reference materials to identify the factors that contribute to thermal comfort in green open spaces in Makassar City. This study aims to analyze the thermal comfort of some green open spaces in Makassar City. The methodology of this research involves a field survey that measures climate factors such as temperature, humidity, sunlight intensity, noise, and wind speed. Thus, it can be concluded that if increasing the urban forest area in urban areas will have a positive impact on comfort, improve air quality, water, soil, and biodiversity, as well as enhance public health and welfare. Enhancing urban forests requires an approach that involves good urban planning, supportive policies, community participation, and the adoption of green technologies across the board, particularly in Makassar City.